2009
DOI: 10.1177/0309133309338660
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of A-tents (pop-ups), sheet structures, and associated forms

Abstract: A-tents are also known as pop-ups and by several other local names. They consist of raised slabs or plates of various thicknesses and origins. Laminae are caused by weathering, and spall plates or slabs may be caused in part by freeze-thaw acting on water held in pre-existing partings which are, however, like the sheet fractures that defi ne the thicker sheet structures, probably of tectonic origin. A-tents are the result of the buckling of such laminae, plates and slabs. Again, tectonism in the form of compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Vidal Romani and Twidale (1999) argue that the stress is of tectonic origin, whereas the authors of this review argue (notably in Lachassagne et al 2011 and) that this compressive stress is due to the weathering process at the time it occurred. However, briefly, it is observed that Vidal Romani and Twidale (1999), and also Twidale and Bourne (2009), do not demonstrate convincingly that the compressive stress that creates(ed) the sheet fractures are of tectonic origin. They propose this as a hypothesis (and use often the conditional argument), that, to the authors' opinion, is far from being formally demonstrated.…”
Section: The Fractured Layer and Its Associated Hydrodynamicalmentioning
confidence: 97%
See 1 more Smart Citation
“…Vidal Romani and Twidale (1999) argue that the stress is of tectonic origin, whereas the authors of this review argue (notably in Lachassagne et al 2011 and) that this compressive stress is due to the weathering process at the time it occurred. However, briefly, it is observed that Vidal Romani and Twidale (1999), and also Twidale and Bourne (2009), do not demonstrate convincingly that the compressive stress that creates(ed) the sheet fractures are of tectonic origin. They propose this as a hypothesis (and use often the conditional argument), that, to the authors' opinion, is far from being formally demonstrated.…”
Section: The Fractured Layer and Its Associated Hydrodynamicalmentioning
confidence: 97%
“…Tröger (U. Tröger, Technische Universität Berlin, personal communication, 2020) raised attention to the fact that Twidale and collaborators "demonstrated" the tectonic origin of the sheet fractures, constituting the fractured layer mostly in granites. As part of this review, several of their papers were studied, and Vidal Romani and Twidale (1999) and Twidale and Bourne (2009) were found to be the most relevant and recent publications on this topic. First, Vidal Romani and Twidale (1999) convincingly show that sheet fractures are due to compressive stress, more precisely horizontal compressive stress.…”
Section: The Fractured Layer and Its Associated Hydrodynamicalmentioning
confidence: 99%
“…Existing data, however, come from observations of static landscapes where exfoliation sheets (referring to the detached slabs of rock produced by exfoliation) and domes reside as relict features 2 , 6 . For example, curious tent-like structures—common on domes—have only qualitatively been explained as by-products of compression 9 , 14 , 15 . Yet, as an example of rock fracture, exfoliation is perplexing and raises questions concerning the temporal scale over which it occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Twidale & Bourne 2000), others have developed gradually. This has been demonstrated over almost a century by a family monitoring a site near their homestead in the Darling Ranges of Western Australia (Twidale & Bourne 2003, 2009. The hydrophilic, swelling or cracking clays of American literature, in South Australia are known as 'Bay of Biscay' soils.…”
Section: Synonymsmentioning
confidence: 99%